2014
DOI: 10.1542/peds.2014-0828
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Guidelines for Glucose Assessment in Starting Second-Generation Antipsychotics

Abstract: OBJECTIVES: In 2003, the US Food and Drug Administration issued warnings about hyperglycemia and diabetes with second-generation antipsychotics (SGAs); guidelines have recommended metabolic screening since 2004. However, little is known of contemporary practices of glucose screening among youth initiating SGAs. Our objective was to evaluate baseline glucose assessment among youth in the Mini-Sentinel Distributed Database starting an SGA. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
(40 reference statements)
8
30
1
Order By: Relevance
“…As part of the ongoing metformin for overweight and obese children with bipolar spectrum disorders treated with SGA (MOBILITY) study (PCS-1406-19276; ClinicalTrials.gov identifier: NCT02515773), a randomized, large, simple pragmatic clinical trial examining metformin as standard of care for overweight and obese youth (8-19 year old) with past or present bipolarspectrum illness who require treatment with SGAs, rates of metabolic monitoring are being evaluated as part of the battery of outcome measures. Interim findings suggest suboptimal baseline monitoring of subjects (66.9% any lab, 66.1% glucose, 61.0% triglycerides, and 60.4% cholesterol), although higher than previously published studies that have reported rates of glucose (15%-50%) and lipid (13%) screenings in youth initiating SGA treatment (Morrato et al 2010;Raebel et al 2014). Although the MOBILITY trial is intended to reflect ''real-world'' clinical practice through its pragmatic study design, there is likely additional attention to laboratory tests compared with usual care because of the study's emphasis on metabolic monitoring.…”
Section: Introductionmentioning
confidence: 65%
“…As part of the ongoing metformin for overweight and obese children with bipolar spectrum disorders treated with SGA (MOBILITY) study (PCS-1406-19276; ClinicalTrials.gov identifier: NCT02515773), a randomized, large, simple pragmatic clinical trial examining metformin as standard of care for overweight and obese youth (8-19 year old) with past or present bipolarspectrum illness who require treatment with SGAs, rates of metabolic monitoring are being evaluated as part of the battery of outcome measures. Interim findings suggest suboptimal baseline monitoring of subjects (66.9% any lab, 66.1% glucose, 61.0% triglycerides, and 60.4% cholesterol), although higher than previously published studies that have reported rates of glucose (15%-50%) and lipid (13%) screenings in youth initiating SGA treatment (Morrato et al 2010;Raebel et al 2014). Although the MOBILITY trial is intended to reflect ''real-world'' clinical practice through its pragmatic study design, there is likely additional attention to laboratory tests compared with usual care because of the study's emphasis on metabolic monitoring.…”
Section: Introductionmentioning
confidence: 65%
“…However, the content and schedule of the physical evaluations and follow-up practices of SGA medications have been diverse in child psychiatric clinical work (7,39,(44)(45)(46), as was also observed in this study. Only about one-third of the study patients had undergone a physical evaluation at SGA initiation.…”
Section: Discussionmentioning
confidence: 54%
“…Recommendations and follow-up protocols seem to be helpful in clinical work and appear to increase monitoring and possibly have an effect on prescribing practices (7,43,44). Despite the already existing recommendations, there has been a lag in the translation of research evidence into clinical practice (39,45). Rates of metabolic monitoring of SGA have been low according to several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic medications should be used only when required (eg, due to failure of other therapeutic options or absence of clinically appropriate alternatives), prioritising presumably less metabolically risky agents, and adhering to metabolic screening (at baseline) and monitoring (during treatment) recommendations. Current evidence suggests that pretreatment glucose screening recommendations for paediatric patients are not being followed 5. Sex differences in the risk of new-onset type 2 diabetes are interesting, but metabolic screening and monitoring practices should not differ according to patient sex.…”
Section: Do These Results Change Your Practices and Why?mentioning
confidence: 99%